Antimicrobial and Anti-inflammatory Effects of a Novel Peptide From the Skin of Frog Microhyla pulchra - Tian, Maolin; Liu, Junfang; Chai, Jinwei; Wu, Jiena; Xu, Xueqing (Frontiers in Pharmacology, 2021)
Brevinins are an important antimicrobial peptide (AMP) family identified in the skin of Ranidae frogs and generally contain a characteristic ranabox structure at their C-terminal sequence. Herein, a novel AMP named brevinin-2MP has been identified from the skin of the frog Microhyla pulchra by molecular cloning. Brevinin-2MP (GVITDTLKGVAKTVAAELLRKAHCKLTNSC) with high amphipathic α-helix in SDS solutions can destroy bacterial cell membrane and kill microbes. Furtherly, brevinin-2MP has been found to inhibit LPS-induced expression of pro-inflammatory NO, MCP-1, IL-6 and TNF-α via binding unidentified targets on cell membrane and consequently suppressing activation of MAPK/NF-κB signaling cascades induced by LPS in RAW 264.7 cells. Consistently, brevinin-2MP significantly alleviates the acute inflammatory response in carrageenan-induced mice paw. In conclusion, brevinin-2MP with anti-inflammatory and antimicrobial properties will be an ideal candidate drug molecule for bacterial inflammation treatment.